2016
DOI: 10.5935/1678-9741.20160086
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage in Human Aorta of Patients with Advanced Aortoiliac Occlusive Disease

Abstract: IntroductionOxidative stress seems to be a role in the atherosclerosis process, but research in human beings is scarce.ObjectiveTo evaluate the role of oxidative stress on human aortas of patients submitted to surgical treatment for advanced aortoiliac occlusive disease.MethodsTwenty-six patients were divided into three groups: control group (n=10) formed by cadaveric organ donors; severe aortoiliac stenosis group (patients with severe aortoiliac stenosis; n=9); and total aortoiliac occlusion group (patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…dROMs are hydroperoxydes, meaning reactive oxygen metabolites that allow to directly evaluate oxidative stress levels [61,62]. SOD and GPX are antioxidant enzymes whose activity measurement indirectly allows to quantifying the response to oxidative stress [63,64]. In the present study, significantly higher levels of GPX and dROMs were observed in captive BR compared to WR, suggesting a higher degree of oxidative stress in captive BR.…”
Section: Discussionmentioning
confidence: 47%
“…dROMs are hydroperoxydes, meaning reactive oxygen metabolites that allow to directly evaluate oxidative stress levels [61,62]. SOD and GPX are antioxidant enzymes whose activity measurement indirectly allows to quantifying the response to oxidative stress [63,64]. In the present study, significantly higher levels of GPX and dROMs were observed in captive BR compared to WR, suggesting a higher degree of oxidative stress in captive BR.…”
Section: Discussionmentioning
confidence: 47%
“…In another study, the aforementioned authors compared the aortic tissues, which were obtained from AOD patients (severe stenosis or occlusion) with the aortic tissues obtained from cadaveric organ donors. [33] They reported that, in addition to the ROS levels, the SOD and CAT activities also significantly increased in the patients compared to the control group (p<0.05). In this study, the authors concluded that the antioxidant enzyme activity increased to compensate the increased ROS levels, depending on the NADPHoxidase activity.…”
Section: Discussionmentioning
confidence: 96%
“…In the previous studies, the prooxidant-antioxidant status in the AIOD patients was insufficiently investigated. Although some researchers indicated that ROS levels significantly increased with AIOD severity, no literature data has analyzed AGEs levels in the blood of the AIOD patients [30]. The same applies to AAA patients.…”
Section: Discussionmentioning
confidence: 99%